Pre-prescription review system improves prescription safety, efficiency, and cost-effectiveness in pediatric outpatients: a western China study - Yang, Bin; He, Junyan; Li, Qianbo; Wang, Xiuling; Song, Lin (Frontiers in Pharmacology, 2025)
ObjectiveThe study’s objective is to investigate the prescription rationality rate, time efficiency, and estimated economic benefits of a pre-prescription review system (PPRS) in pediatric outpatients in a 5-year retrospective study in western China.MethodThis retrospective before-after study compared data from two phases: pre-intervention phase (2019: PPRS not yet implemented), and post-intervention phase (2020–2023: PPRS fully operational). The study evaluated three key endpoints: primary endpoint was the prescription rationality rate; the secondary endpoints were time efficiency (interval from prescription to drug dispensing) and suggested economic benefits (estimated benefit-cost ratio). Descriptive analyses were conducted to investigate the prescription rationality rate before and after PPRS implementation. The time interval from prescription to drug dispensing was analyzed from 2019 to 2023 using one-way ANOVA. Suggested economic benefit was evaluated under the healthcare system perspective with estimated benefit-cost ratio.ResultsThe PPRS implementation was correlated with an increase in the rational prescription rate in outpatient department from 91.19% in 2019 to 98.79% in 2023 and a reduction in time interval from prescription to dispensing from 19.59 min in 2019 to 16.33 min in 2020 (p < 0.0001), with sustained lower levels from 2020 through 2023 (16.07 min–16.33 min). Conducting the PPRS was also associated with indicated cost savings, with an estimated benefit-to-cost ratio exceeding 1.64.ConclusionThe implementation of PPRS was associated with enhanced prescription rationality and time efficiency in pediatric outpatient settings while indicating potential economic benefits. This PPRS is worthy of popularization but needs to be validated across diverse populations and institutions.